2021
DOI: 10.3389/fimmu.2020.606893
|View full text |Cite
|
Sign up to set email alerts
|

TRPM7 Kinase Is Essential for Neutrophil Recruitment and Function via Regulation of Akt/mTOR Signaling

Abstract: During inflammation, neutrophils are one of the first responding cells of innate immunity, contributing to a fast clearance of infection and return to homeostasis. However, excessive neutrophil infiltration accelerates unsolicited disproportionate inflammation for instance in autoimmune diseases such as rheumatoid arthritis. The transient-receptor-potential channel-kinase TRPM7 is an essential regulator of immune system homeostasis. Naïve murine T cells with genetic inactivation of the TRPM7 enzyme, due to a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 49 publications
2
24
1
Order By: Relevance
“…TRPM7 activation leads to neuron death via mediating Ca 2+ overload and ROS production, with suppression of TRPM7 significantly reducing oxidative damage [ 43 , 44 ]. Further, the channel-kinase of TRPM7 is functionally expressed in neutrophils, playing an essential role in neutrophil recruitment during inflammation [ 45 ]. Our previous study found that blockade of TRPM7 had a protective effect on RA articular cartilage destruction [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRPM7 activation leads to neuron death via mediating Ca 2+ overload and ROS production, with suppression of TRPM7 significantly reducing oxidative damage [ 43 , 44 ]. Further, the channel-kinase of TRPM7 is functionally expressed in neutrophils, playing an essential role in neutrophil recruitment during inflammation [ 45 ]. Our previous study found that blockade of TRPM7 had a protective effect on RA articular cartilage destruction [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRPM7 is a bifunctional protein fusing a divalent cations channel to a C-terminal serine/threonine kinase. Since cloned two decades ago, TRPM7 has emerged as new therapeutic target and is associated with tumor progression, anoxic neuronal death, tissue fibrosis, giant platelet disorders, neutrophil recruitment, and production of reactive oxygen species [ 30 , 31 ]. Our group has long been focusing on the study of TRPM7’s potential as a therapeutic target in glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the TRPM7 channel, a recent study reported a role for TRPM7 kinase in neutrophil migration [84]. Using the kinase inhibitor TG100-115, chemotaxis of neutrophils towards CXCL8 was significantly attenuated, possibly through the Akt/ mTOR signalling pathway [84]. This opens new doors for study of the function of TRPM7 kinase.…”
Section: Regulation Of Trpm7 In Neutrophilsmentioning
confidence: 99%
“…Calcium flicker was shown to regulate fibroblast migration, and this may also be key to the regulation of neutrophil migration by TRPM7, but more research is needed to establish these results. In addition to the TRPM7 channel, a recent study reported a role for TRPM7 kinase in neutrophil migration [84]. Using the kinase inhibitor TG100-115, chemotaxis of neutrophils towards CXCL8 was significantly attenuated, possibly through the Akt/ mTOR signalling pathway [84].…”
Section: Regulation Of Trpm7 In Neutrophilsmentioning
confidence: 99%